Academic Motivation and Achievement in Undergraduate Students of the Medical Program, Faculty of Medicine, Tanjungpura University, during the COVID-19 Pandemic - Imanda Yandion; Iit Fitrianingrum; Sari Eka Pratiwi (Juxta: Jurnal Ilmiah Mahasiswa Kedokteran Universitas Airlangga)
Introduction: Academic motivation is said to be correlated to academic achievement. The coronavirus disease (COVID-19) pandemic has led to a distance learning policy allowing students to continue their education. Distance learning has several impacts that can result in students' academic motivation. Therefore, it affects academic achievement. This study examined the relationship between academic motivation and achievement in undergraduate students of the Medical Study Program, Faculty of Medicine, Tanjungpura University, during the COVID-19 Pandemic.